The Influence of Motivation on English Language Learning: Insights from SLA Research - SESHAGIRI, H.; Sai Krishna , Kota (International Journal of Psychosocial Rehabilitation, 2024)
Motivation is widely recognized as a critical factor in Second Language Acquisition (SLA), influencing the success and persistence of learners in mastering a new language. This study explores the role of motivation in English language learning, drawing on insights from prominent SLA theories and empirical research. The paper examines different types of motivation, including intrinsic, extrinsic, instrumental, and integrative, and their impact on learners' language proficiency and engagement. Additionally, it highlights how motivational factors interact with other variables, such as age, learning environment, and cultural context. The findings underscore the importance of fostering motivation through tailored teaching strategies and learner-centered approaches. By synthesizing theoretical perspectives and practical implications, this research contributes to a deeper understanding of how motivation shapes the process of English language acquisition and offers recommendations for educators and policymakers to enhance learner outcomes.